The complex nature of power and language - Inan, Dilek (ELOPE (Ljubljana), 2016)
The purpose of the paper is to examine the dynamic relationships between language and power in The City (2008), which was written by the groundbreaking playwright Martin Crimp. In a systematic and intentional way, Crimp's language resists the established conventional standards and challenges any typical expectations for dramatic discourse. Crimp deconstructs language and dismantles its authorial guidance. He employs stimulating and inventive dialogues through word games and language strategies and devices such as repetitions, interruptions, silences and pauses, denial, concealment, other enhancement, negation, formulation, topic-shift and turn-taking. Crimp exploits language through effective and energetic rhythm, structure and form in order to depict the ethical disasters of the contemporary world. The playwright breaks the traditional dramatic form, replacing it with his unique device where the language does not communicate meaning but acts as a means of articulating power through verbal strategies.
Keywords: angleška književnost; Crimp, Martin, 1956-; jezik; Language; literarne študije; moč; power; sodobna britanska dramatika